The Power of Youtube to Improve Listening Skills - Widiya Mentari Hakim; Siti Harahap (JELT : Journal of English Education, Teaching and Literature, 2024)
This research is motivated by questionnaire data which shows the achievement of student learning outcomes in the material "The Power of YouTube to Improve Listening Skills". researchers conducted action research aimed at improving student learning outcomes. The objectives to be achieved in this research include 1.) to determine the strength of YouTube in the English learning process in improving listening skills, and 2.) to determine the increase in student learning outcomes by using YouTube. This research was conducted on students at the State Islamic University of North Sumatra in the English Language Education Department. This research measures how strong the role of YouTube is in the teaching and learning process. The research results show that the respondents agree that YouTube can improve listening skills with a variety of different content that the respondents access. With this learning method, students get more interesting learning and can improve good learning outcomes, not boring and easy for students to accept. From this research, it is recommended for readers to use learning methods using YouTube.